ANTI-INFLAMMATORY THERAPY IN THE PREVENTION OF PERIODONTAL DISEASES TISSUE. MYTHS OR THEIR EFFICIENCY (World Science, 2018)
We have considered and proved that phospholipase model periodontitis considerably aggravates bone resorption of the alveolar process and flow in rats. Also in modeling disease decreased antioxidant defenses. At the same time as the application of complex preventive effectively prevent violations in the pulp, gums, alveolar process, prevented bone resorption of the alveolar process and the development of inflammatory processes in animal models.